BASE TRANSCEDENTAL VALUE ON JUDGE’S DECISION (Study of Basic Perspective of Pancasila State) - Nurul Huda; Khudzaifah Dimyati (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Pancasila is the state fundamental norm that is not formed by a higher norm. The highest expectation of justice seekers is fair verdict. The criticisms addressed to the judges persist due to gap between the judge's verdict and the values of justice the public hoped for. Viewed from the philosophical perspective, the first principle is vertical dimension (hablumminallah) while the second one is horizontal dimension (hablumminnas). This paper examines transcendental value in judge's decision. This research uses qualitative approach method through inductive conceptualization approach. The research intended to investigate the judges' rulings subsequently opposed to the juridical, sociological and philosophical transcendental values found its relevance to the rechtidee of the Indonesian nation. The results show that in practice, there is a tendency that judges' rulings emphasize on procedural justice rather than substantial justice. Whereas, if we comprehend the State Policy and the constitution, the judges verdicts ideally cannot be separated from its base namely transcendental values.Keywords: Judge's Verdict, Pancasila, Transcendental Value